S118 Incidence And Severity Of Chronic Thromboembolic Pulmonary Hypertension Following The Introduction Of A One-stop Clinic For Acute Pulmonary Embolism. (10th November 2014) - De Foneska, D; Condliffe, R; Elliot, CA; Hughes, R; Hurdman, J; Ghafur, S; Schofield, M; van Veen, JJ; Maclean, R; Kiely, DG
Abstract : Introduction: The management and follow-up of pulmonary embolism (PE) is delivered by various specialities resulting in both under and over investigation for suspected chronic thromboembolic pulmonary hypertension (CTEPH). To standardise our approach to long-term PE management a "one-stop" clinic was established in Sheffield in March 2010 to review all patients approximately 3 months after their presentation with acute PE. The aim of this study was to evaluate the incidence and severity of CTEPH identified from a one-stop clinic using an investigative strategy based on careful clinical assessment Methods: Consecutive patients attending the one-stop PE clinic following hospital admission with acute PE were identified. During the one-stop consultation a haematologist and respiratory physician reviewed the patient jointly. The need for further investigation was based on clinical assessment. CTEPH was defined as mean pulmonary artery pressure (mPAP) at right heart catheterisation ≥25 mmHg and required multimodality imaging (isotope perfusion scanning, CT pulmonary angiography and MR imaging including MRA and MR perfusion mapping) demonstrating classical features of CTEPH. Results: Over a 3-year period between March 2010 and March 2013, 616 patients (mean age 67.7 years, 50% male) attended the one-stop PE clinic approximately 3 months following their acute presentation. 16 patients were diagnosed with CTEPH. An overall diagnostic rate of CTEPH of 2.6% for patients seen at the clinic and an annual incidence of 8.9/million/year was observed based on a referral population of 600, 000. This compares to an annual incidence of CTEPH of 4.8/million/year in patients referred to the SPVDU over the same time period, based on a referral population of 15 million. The 16 patients with CTEPH had mPAP 37 ± 11 mmHg, pulmonary vascular resistance (PVR) 362 ± 240 dynes, significantly lower than patients with CTEPH diagnosed at the SPVDU until 2010 (n = 242) mPAP 48 ± 11 mmHg and PVR 735 ± 389 dynes (Hurdman et al Eur Respir J 2012:39(4):945–955). Conclusion: Introduction of a one-stop PE clinic for routine follow-up of patients with acute pulmonary embolism identifies patients with higher rates of CTEPH with less severe pulmonary haemodynamic changes.